Integrating advanced synthesis techniques and AI-driven approaches with nanofiber technology: A state-of-the-art approach to wound care management - Nisha Shankhwar; Awadhesh Kumar Verma; Ashab Noumani; Tanya Singh; Kalakuntla Sriharshitha Rao; Vivekanand; Neeta Raj Sharma; Satyendra Singh (Next Nanotechnology)
Wound healing is a complicated clinical problem when common topical therapies and dressings are insufficient for different kinds of wounds, such as burns, surgical, and chronic wounds. This review emphasizes the ground-breaking potential of nanofiber technology, a novel approach that imitates the extracellular matrix (ECM) to promote targeted therapeutic administration and support cellular regeneration. Because of their structural compatibility with skin tissue, nanofiber dressings enhance natural healing, maintain optimal moisture levels, and significantly reduce the risk of infection. The comprehensive analysis include methods for producing nanofibers, crucial design components, and applications appropriate for different wound types. Concurrently, the integration of the Internet of Things (IoT), Artificial Intelligence (AI), and Machine Learning (ML) is revolutionizing wound care. Because of this, ''smart'' dressings with real-time monitoring, dynamic data processing, and precise therapeutic release capabilities have been developed, allowing medical personnel to provide more individualized and responsive care. These developments can potentially revolutionize wound care through timely interventions and improving patient outcomes. Although combining nanofiber technology with AI-powered smart dressings seems promising, there are still barriers in implementing these developments for general clinical applications. This review offers a comprehensive overview of current research and the critical role nanofiber technology plays in enhancing wound care. We plan to highlight the path for robust, scalable, and customized wound treatments by identifying key implementation barriers and exploring potential developments. Nanofibers, with their exceptional capabilities, signify a profound advancement in wound healing, offering new optimism for improved patient recovery and enduring health benefits.